Estudio de mercado para determinar el posicionamiento de Reyleche en el cantón Quevedo 2010 - Lutuala Chacha, María Elena (2011)
This research was conducted in supermarkets Quevedo Canton, which is dedicated to the distribution of milk. The research work lasted for 6 months. One of the most significant activities is the distribution in the different sites of local outlets and advertising strategies to take possession of the product in the target market, hence this research was the objective: To determine the position of the Reyleche in Quevedo market, and, knowing the tastes and preferences, acceptance of the product on the market Reyleche Quevedo, know the place prefers cunsumidor when buying milk, presenting Reyleche define what the consumer prefers, identify the brand of milk is among the best consumer Quevedo Canton. The address was oriented methodological research: From Field, which used the techniques of survey, interview and observation where the methods applied by age and focus groups, to support the hypothesis of the problem and the information was obtained through primary and secondary source. For Reyleche product positioning, consumers were surveyed, we used a questionnaire which highlights the brand Reyleche is in third place position in relation to competition in the market, low product acceptance Reyleche , is due to consumer perception to pack (case) is not attractive to the consumer, to a low diffusion of the slogan and product quality, and that consumers prefer to buy milk product in supermarkets Reyleche Quevedo Canton. The presentation of milk has greater acceptance by consumers is the liter, and that the brand of milk that is among the best by the consumer of the canton is the brand Dairy Quevedo. The Reyleche ranks third in the local market, women of 20-30 years are the most consumed milk according to the results obtained, it is because according to the medical suggestions, if for some reason have failed achieve a calcium adequate reserves for 30 years or accelerate their losses from the age of 30 appears osteoporosis.